Peran Bawaslu Dalam Menangani Kasus Politik Uang Sebagai Tindak Pidana Pemilu - Anggy Dwi Septiani Vindya Nabila Syafia; Mega Dewi Ambarwati (JURNAL ILMIAH NUSANTARA, 2025)
The Election Supervisory Agency (Bawaslu) plays a crucial role in maintaining the integrity of elections in Indonesia, particularly in addressing cases of vote-buying that undermine the principles of democracy and justice. Vote-buying results in unfairness in elections, where candidates with greater financial resources can buy votes, while more qualified candidates are marginalized. This study aims to analyze Bawaslu's role in addressing vote-buying practices and to evaluate the gap between public expectations for fair elections and the existing reality. The methodology used is a qualitative approach through document studies. The findings indicate that Bawaslu conducts monitoring, investigations, public education, and coordination with other agencies to reduce vote-buying practices. However, significant challenges remain in law enforcement and raising political awareness among the public. Recommendations are provided to strengthen Bawaslu's oversight effectiveness and promote improvements in electoral policies.